PENDAMPINGAN REMAJADUSUNKENAIBAN DAN PENCIL, DESAKENAIBAN, JUWIRING, KLATEN,JAWA TENGAH - Siti Hapsah Isfardiyana (UII, 2014)
Adolescents as the future generation has an important role in society, but over timealot of teenagers who are doing exactly deviate such as brawling and using drugs. Teensneed to know that adolescence is a vulnerable period of preparation that needs to getthrough and build character well. So the need for special activities to provideinformation to adolescents on adolescent problems, the importance of consultation indealing with teen issues, what will be facing youth and how best to resolve theirproblem. With their education about adolescent counseling, teenager will be moreaware of what isgoing passed in his youth, just anything that might be perceived, anyirregularities that may occur, and what to do when they are facing particular problems.